New Insights Into the Regulatory Roles of Extracellular Vesicles in Tumor Angiogenesis and Their Clinical Implications - Huang, Maohua; Lei, Yuhe; Zhong, Yinqin; Chung, Chiwing; Wang, Mei; Hu, Min; Deng, Lijuan (Frontiers in Cell and Developmental Biology, 2021)
Angiogenesis is required for tumor growth and development. Extracellular vesicles (EVs) are important signaling entities that mediate communication between diverse types of cells and regulate various cell biological processes, including angiogenesis. Recently, emerging evidence has suggested that tumor-derived EVs play essential roles in tumor progression by regulating angiogenesis. Thousands of molecules are carried by EVs, and the two major types of biomolecules, noncoding RNAs (ncRNAs) and proteins, are transported between cells and regulate physiological and pathological functions in recipient cells. Understanding the regulation of EVs and their cargoes in tumor angiogenesis has become increasingly important. In this review, we summarize the effects of tumor-derived EVs and their cargoes, especially ncRNAs and proteins, on tumor angiogenesis and their mechanisms, and we highlight the clinical implications of EVs in bodily fluids as biomarkers and as diagnostic, prognostic, and therapeutic targets in cancer patients.